ГОФМАНОВСКИЙ «СЛЕД» В ПОЭМЕ А. АХМАТОВОЙ «ПУТЕМ ВСЕЯ ЗЕМЛИ» (Filološke pripombe, 2019)
The “Gofman’s» part of long poem «The Way of All the Earth» is analyzed in the article. The author pays attention on conditional-associative aspect of the long poem: signs, codes, dreams, symbols, doubles, mirror-images etc. Learning about role of the Gofman’s traditions in the long poem, the author demonstrates that paradoxes of midnight «gofmaniana” help to understand the world of ominous century.